Enhanced activity and durability of platinum anode catalyst by the modification of cobalt phosphide for direct methanol fuel cells. (10th December 2015) - Li, Xiang; Wang, Hongjuan; Yu, Hao; Liu, Ziwu; Wang, Haihui; Peng, Feng
Graphical abstract: A novel Pt/CoP/CNTs electrocatalyst with has been designed and prepared, which exhibits high activity and stability for methanol oxidation reaction. Highlights: Pt-cobalt phosphide catalyst supported on carbon nanotubes (Pt/CoP/CNTs) is designed. Pt/CoP/CNTs exhibit high activity and stability for methanol oxidation reaction(MOR). The effect of CoP content on electrocatalytic performances for MOR is studied. CoP decreases the Pt particle size and increases the electrochemical surface areas. The interaction between Pt and CoP is evidenced by X-ray photoelectron spectroscopy. Abstract: In this study, carbon nanotubes (CNTs) supported Pt-cobalt phosphide (CoP) electrocatalyst (Pt/CoP/CNTs) is designed and prepared for methanol oxidation (MOR) for the first time. The modification of CoP decreases the Pt particle size significantly and increases the electrochemical surface areas due to the interaction between Pt and CoP, which is evidenced by transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Among all these catalysts, Pt/4%CoP/CNTs catalyst exhibits the best MOR activity of 1600 mA mg −1 Pt, which is six times that of Pt/CNTs. Moreover, this catalyst also exhibits the higher onset current density and steady current density than the other Pt-based catalysts. The work provides a promising method to develop the highly active and stable Pt-based catalyst for direct methanol fuel cells.